2022-RA-937-ESGO Rucaparib MAintenance after bevacizumab maintenance following carboplatin based chemotherapy in primary ovarian cancer. (20th October 2022) - Braicu, Elena-Ioana; Pietzner, Klaus; Dysarz, Jessica; Rogmans, Gunther; Wimberger, Pauline; Egger, Eva; Gerber, Jens; Eichbaum, Michael; Heitz, Florian; Kupec, Tomas; Koch, Martin Christoph; Deryal, Mustafa; et al.
Abstract : Introduction/Background: Ovarian cancer (OC) is the fifth most common cause of death from cancer in women in Europe, with most patients being diagnosed in advanced stages. The most common histological subtype is high grade serous OC, which is characterised by deficiency in homologous recombination. The current standard therapy for advanced OC patients is debulking surgery, followed by platinum based chemotherapy and bevacizumab (bev), followed by maintenance therapy with bev or monotherapy with PARP inhibitors (PARPi). The anticancer effects of PARPi seem to be increased by the addition of antiangiogenic drugs. Preclinical data showed increased HRD in tumours pre-treated with bev, and clinical trials showed a benefit of the combination of antiangiogenic drugs and PARPi vs. PARPi alone. Hence, in this placebo-controlled study we will evaluate rucaparib maintenance following bevacizumab maintenance for the treatment of advanced primary high grade BRCAwt OC (centrally tested by NGS analysis). Methodology: This study will randomise 190 patients with histologically confirmed advanced (FIGO stage IIIA- IV) high grade serous or high grade endometrioid OC, fallopian tube cancer, primary peritoneal cancer or clear cell carcinoma of the ovary at the ration of 2:1 to receive either rucaparib 600 mg BID or placebo as maintenance therapy following first line chemotherapy with 6 cycles of Carboplatin/Paclitaxel and at least 12 months of bevacizumab. Subsequent maintenance therapy with rucaparib will continue for 24 months or until disease progression, unacceptable toxicity, or withdrawal. Randomisation is stratified by surgery planned time point (neoadjuvant vs. adjuvant), surgical outcome (R0 vs R1), response to chemotherapy followed by bev (CR/NED vs. PR/SD) and study center. Primary endpoint is PFS per RECIST v1.1. Secondary endpoints are PFS2, quality of life, daily activity, time to next medical intervention, time to next subsequent therapy, safety assessments and OS. So far 35 patients are randomised in the study. Results: Conclusion: